The self according to others: Explaining social preferences with social approbation - Oswin Krüger Ruiz (Economic Thought, 2020)
In past decades, significant work in behavioural economics has decisively revealed the limitations of the human agency model known as Homo Economicus, whereby humans are purely driven by material self-interest.1 These behavioural findings are, however, far from integrated in mainstream economic theory, which builds heavily on the neoclassical tradition. Unbeknown to modern economics, Bernard Mandeville and Adam Smith already proposed a richer model of human agency in which choices also depend on the desire for social approbation. The social approbation mechanism complements material self-interest and provides a more diverse toolset, which is able to explain social preferences.2 Mainstream economic agency confines the study of human action to an artificially-limited spectrum because it reduces society to atomistic individuals who maximise one all-purpose measure of value: utility, which is often instrumented by consumption. Collective action is therefore only sustainable where material incentives are in place, as the economic agent rides for free unless financially penalised. To explain pro-social behaviour from the standpoint of self-interest, Mandeville and Smith proposed that agents also maximise social approbation, which conveys incentives to act pro-socially because the desire for others' approval encourages compliance with social norms. The upshot for collective action is that, assuming social norms represent common interests, approval from others provides an extrinsic motive for pro-social behaviour. I formalise the mechanism by proposing a simple utility function in which agents maximise social approbation as well as material self-interest.
Keywords: B41; D16; B12; D91; B50; 330